Model Fisik Fenomena Terbentukn Ya Tidal Flat Pada Lahan Gambut Kepulauan - Adri Patria Ganda; Rinaldi Rinaldi; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The phenomenon of the formation of tidal flats is a unique phenomenon which is very interesting to study. The purpose of this study was to analyze the wave characteristics of the island peatlands and the tidal flat formation process. The method used in this research is bed load simulation and one-way waves with variations in wave period, wave height and wavelength. Simulations were carried out in the Hydrotechnic Laboratory using a flume measuring 500cm x 7.6cm x 25cm, Motoric Wave Generator, and Velocimeter. The results showed that the bed profile changed dynamically moving back and forth, and tidal flats were formed at the 5th and 6th hours with a length of 9.9 cm offshore then the tidal flat was abrasive. Keywords: Bed Load, Tidal Flat, Wave characteristics